Kyrgyz Republic : Staff Report for the 2006 Article IV Consultation, Third Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Structural Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2007)
The Kyrgyz authorities have maintained macroeconomic discipline in recent years, despite a challenging political environment. This 2006 Article IV Consultation highlights that the economic activity is rebounding in 2006, with year-over-year real GDP growth of 3.2 percent through September, after a slight contraction in 2005. Inflation is projected to rise slightly to just below 6 percent during 2006. Remonetization has gathered pace in recent years, but the financial system remains relatively shallow by international standards. Comprehensive financial reforms are under way and are slated to gain momentum under the IMF-supported program.